The Impact Of Moving From Sacs Level I To Level Ii Status On Faculty Employment In The Florida College System - Broeker, Christine (2013)
The State of Florida legislatively authorizes Florida community colleges to confer workforce-oriented bachelor’s degrees. As part of the legislation, community colleges are required to achieve Level II (baccalaureate-granting) status through Florida’s regional accreditor, the Southern Association of Colleges and Schools-Commission on Colleges (SACS-COC). When moving from SACS Level I to II, former community colleges need to meet the SACS CS 3.7.1 (Qualified Faculty), which requires that faculty who teach baccalaureate courses hold the minimum of a master’s degree in field. Further complicating matters, as baccalaureate granting institutions, colleges must also comply with CS 3.5.4, requiring 25% of course hours in the baccalaureate degree major to be taught by terminally-degreed faculty. The purpose of this study was to identify what issues related to faculty credentials, if any, have been observed by Florida’s community colleges as part of the process to gain SACS-COC Level II status. Results were analyzed through the lens of Travis Hirschi’s Social Control Theory. The results of this study indicate that colleges have reported changes in faculty employment after implementing the community college baccalaureate. The most common types of changes included requirements for faculty to complete additional graduate coursework and moving faculty to different programs with different conditions for credentialing. Other types of changes reported included faculty terminations and retirements. The study found strong evidence supporting the notion that finding terminally-degreed faculty is a problem for institutions moving from Level I to Level II status particularly in the fields of nursing and computer science/information technology. iv The findings indicate that as Florida’s community college baccalaureate programs continue to expand, colleges will need to find creative solutions to address SACS CS 3.5.4 requirement of terminal degrees for facult